2022
DOI: 10.1055/a-1830-3962
|View full text |Cite
|
Sign up to set email alerts
|

Pd(II)-Catalyzed, Picolinamide-Aided γ-(sp2)-C–H Functionalization of Racemic and Enantiopure α-Methylbenzylamine and Phenylglycinol Scaffolds

Abstract: In this paper, we report the Pd(II)-catalyzed, picolinamide DG-aided sp2 γ-C-H functionalization and expansion of the library of enantiopure α-methylbenzylamine and phenylglycinol scaffolds. We have shown the synthesis of a wide range of racemic and enantiopure ortho-C-H arylated, alkylated, brominated and iodinated α-methylbenzylamine and phenylglycinol scaffolds. Various racemic and R and S (chiral) sp2 γ-C-H functionalized α-methylbenzylamine and phenylglycinol scaffolds were synthesized with good enantiopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 128 publications
0
13
0
Order By: Relevance
“…Next, we attempted the Pd(II)‐catalyzed C(2)−H benzylation of tyrosine substrate 4 a ‐(DL) with benzyl bromides to obtain the tyrosine‐based diarylmethane scaffolds. Accordingly, the C(2)−H benzylation of 4 a ‐(DL) was attempted using the ortho C−H benzylation conditions (reported by Daugulis, Jiang and used by us earlier) [17,18a,d] . Initially, we performed a few reactions to find suitable conditions for obtaining the C(2) benzylated tyrosine by using a substrate 4 ‐(DL), benzyl bromide (4 equiv) in the presence of the Pd(OAc) 2 catalyst and K 2 CO 3 and PivOH additives in toluene at 110 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we attempted the Pd(II)‐catalyzed C(2)−H benzylation of tyrosine substrate 4 a ‐(DL) with benzyl bromides to obtain the tyrosine‐based diarylmethane scaffolds. Accordingly, the C(2)−H benzylation of 4 a ‐(DL) was attempted using the ortho C−H benzylation conditions (reported by Daugulis, Jiang and used by us earlier) [17,18a,d] . Initially, we performed a few reactions to find suitable conditions for obtaining the C(2) benzylated tyrosine by using a substrate 4 ‐(DL), benzyl bromide (4 equiv) in the presence of the Pd(OAc) 2 catalyst and K 2 CO 3 and PivOH additives in toluene at 110 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The β ‐phenylalanine substrate 3 a ‐(RS) was treated with p ‐anisyl iodide ( 5 a ) in the presence of the Pd(OAc) 2 catalyst (10 mol %) and AgOAc additive in toluene or t‐ AmylOH or 1,2‐DCE at 80–110 °C for 48 h (under the conditions used by various groups including Daugulis, Chen, Jiang and our group) [3,7b,d,e,9a] . These reactions yielded the bis C(sp 2 )−H ( ortho ) arylated β ‐phenylalanine 7 a ‐(RS) (terphenyl type β ‐amino acid motif) in 55–65 % yield (entries 1–3, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We then attempted the Pd(II)‐catalyzed, picolinamide‐assisted ortho C−H bromination, iodination and chlorination of β ‐phenylalanine substrates (Scheme 5). Accordingly, β ‐phenylalanine substrate 3 a ‐(RS) and para substituted β ‐phenylalanine substrates 3 b – d ‐(RS) were treated with NBS in the presence of the Pd(OAc) 2 catalyst in 1,2‐DCE at 110 °C for 48 h (under the reported conditions) [7e,9a] . These reactions afforded the corresponding bis C(sp 2 )−H ( ortho ) brominated β ‐phenylalanine derivatives 13 a – d ‐(RS) in 23–62 % yields.…”
Section: Resultsmentioning
confidence: 99%
“…All the yields reported are isolated yields and the yields are not optimized and sometimes there is marginal variation in yields and enantiomeric ratio for the corresponding racemic/enantiopure pairs, this is perhaps based on the collection of pure fractions from the column chromatography based on the TLC and also may be due to inadvertent handling/processing errors of samples. Starting materials used in this work to carry out the Pd(II)‐catalyzed γ ‐C(sp 2 )−H alkoxylation with alcohols are known in the literature (see the supporting information) [12h,i] …”
Section: Methodsmentioning
confidence: 99%
“…A literature survey on the Pd(II)‐catalyzed DG‐aided ortho γ ‐C(sp 2 )−H functionalization of enantiopure α ‐alkylbenzylamine derivatives revealed that limited examples of alkylation, alkynylation, carbonylative cyclization, etc have been documented [12] . Along this line, we recently reported the Pd(II)‐catalyzed picolinamide‐aided ortho ‐C−H arylation/alkylation/halogenation of racemic and enantiopure α ‐methylbenzylamine and phenylglycinol scaffolds involving C−C, C−Br and C−I bond‐forming reactions [12h,i] …”
Section: Introductionmentioning
confidence: 99%